Use of index readability of Flesh (ILF) in manual educative for mastectomized women: methodological study - Mariza Silva Oliveira; Francisco Stélio Sousa; Ana Fátima Carvalho Fernandes (Universidade Federal Fluminense, Escola de Enfermagem Aurora de Afonso Costa, 2009)
The study it objectified to verify the legibility of a directed educative manual to the selfcare one of mastectomizadas women, using the calculation of the Index of Legibility of Flesh (ILF) adapted for the Portuguese language. This index predicts the scholarity level and measures the structural difficulty of the text. One is about a research of methodological development, therefore it aims at in systematic way, to improve an intervention. Research carried through in the April months junho/2006. For the operationalization of the calculation of the ILF, the Automatic Grammatical Copyholder for the Portuguese (ReGra) inlaid in the word processor of a computer in version 2003 used itself, with the separate texts as the sequence presented in the topics of the manual. The literal analysis was made in complete and the organized joined data in a picture. The results had varied of 43 the 64, indices that the manual between the easy and difficult reading classifies. No topic presented ILF between 75-100, considered very easy reading, neither, minor of 25, meaning reading very difficult. As the presented results, the demanded scholarity to understand the manual varies between incomplete complete or average education basic. The principles of legibility and the factors that increase the understanding of the reading must be considered in the production of educative materials. Therefore, it must be attempted against for factors that harm the communication process, adopting and improving mechanisms that facilitate the reading, improve the legibility and motivate the reader. It is given credit that the elaboration and the analysis of the legibility of these educative instruments can stimulate the construction of other didactic materials, especially the area of the nursing.